The Heritage of Islam the flowering of Islamic civilization collection. ([S.l. s.n., 2003)
A catalogue of the collection aimed towards scholars of Islamic history and civilization, particularly to Filipino readers.
"The collection consists of monographs, archival and reference materials."
Keywords: Islamic literature -- Catalogs; Civilization, Islamic -- Sources -- Catalogs